Knowledge, attitudes and actions against cancer of health personnel in Tamaulipas - Velasco Canseco, Francisco Alberto; Valera Rojo , Ana Alejandra; Martínez del Alto , Carlos Alejandro; Mata Bugarín , Emmanuel Alejandro; Martínez Padrón, Hadassa Yuef (Horizonte Sanitario, 2024)
Objectives: Analyze the degree of knowledge of health workers about cancer risk factors, as well as assess their attitudes towards prevention and the actions they take to prevent this disease.Materials and Methods: Retrospective, cross-sectional and analytical study of a Health person in Cd. Victoria, Tamaulipas, in the period from March to April 2023. A descriptive and analytical analysis was carried out.Results: 46.5% of health workers identified having three or more risk factors for cancer. However, only 27.4% could correctly identify three modifiable risk factors. In addition, there was low adherence to the screening guidelines, with only 33.6% answering correctly about the age to perform a mammogram after 40 years of age.Conclusions: These findings support the need for interventions aimed at improving cancer prevention among health workers, which could have a significant impact in reducing the burden of this disease in Mexico.Keywords: Knowledge, Prevention, Cancer.